2013
DOI: 10.1128/cvi.00531-12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Specificity of the Enzyme Immunoassay Test for Coccidioidomycosis Varies According to the Reason for Its Performance

Abstract: The diagnosis of coccidioidomycosis relies heavily on serologic test results in addition to clinical history, physical examination, and radiographic findings. Use of the enzyme immunoassay (EIA) has increased because it is rapidly performed and does not require referral to a reference laboratory, as do complement fixation and immunodiffusion tests. However, interpretation of immunoglobulin M (IgM) reactivity by EIA in the absence of immunoglobulin G (IgG) reactivity has been problematic. We conducted a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…Some research groups have reported elevated rates of false positivity, especially among individuals with IgM-only positive results (3,10). Others have reported that the predictive value of such tests depends on the prior probability of CM for a given patient (13). The current study addresses this question by IgG 44 39 5 IgM 29 14 2 IgG and IgM 7 3 1 Total 80 56 8 Puerto Rico IgG 2 4 0 IgM 18 8 2 IgG and IgM 0 0 0 Total 20 12 2 assessing EIA results from individuals living outside a region of endemicity (Puerto Rico), who are not expected to have been exposed to Coccidioides spp., and comparing the results with those from individuals living in a region of endemicity (Arizona).…”
Section: Discussionmentioning
confidence: 99%
“…Some research groups have reported elevated rates of false positivity, especially among individuals with IgM-only positive results (3,10). Others have reported that the predictive value of such tests depends on the prior probability of CM for a given patient (13). The current study addresses this question by IgG 44 39 5 IgM 29 14 2 IgG and IgM 7 3 1 Total 80 56 8 Puerto Rico IgG 2 4 0 IgM 18 8 2 IgG and IgM 0 0 0 Total 20 12 2 assessing EIA results from individuals living outside a region of endemicity (Puerto Rico), who are not expected to have been exposed to Coccidioides spp., and comparing the results with those from individuals living in a region of endemicity (Arizona).…”
Section: Discussionmentioning
confidence: 99%
“…This relatively common finding (~ 10 % of positive tests) has been the subject of several recent publications with quite discrepant conclusions (false-positive rate range 0-82 %) [73]. In particular, one should question the validity of an isolated positive IgM test in an asymptomatic patient or one without classic symptoms [74]. In general, EIAs should be confirmed with ID and/or CF.…”
Section: Antibody Detectionmentioning
confidence: 97%
“…An enhanced surveillance study suggests that the use of laboratory-only criteria for case reporting, including a single positive EIA test, accurately reflects the burden of disease in Arizona 110. Other reports show that EIA testing has a high false-positivity rate111 and more recent evidence has suggested the performance characteristics of EIA testing varies among different patient groups 112…”
Section: Risk Factors For Infectionmentioning
confidence: 99%